PENGARUH REPUTASI KAP, OPINI AUDIT TAHUN SEBELUMNYA, LIKUIDITAS, SOLVABILITAS, DAN KONDISI KEUANGAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Regina, Diva; Paramitadewi, Hyasshinta Dyah S. L. (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2021)
This study aims to analyze the effect of public accounting firm's reputation, previous year's audit opinion, liquidity, solvency, and financial conditions on going concern audit opinion acceptance. The companies studied were the mining sector listed on the Indonesia Stock Exchange in 2015-2019. This study examines 65 firm years data using logistic regression. The results indicate that the previous year's audit opinion has a positive, while financial conditions have a negative effect on going concern audit opinion acceptance. On the other hand, the public accounting firm's reputation, liquidity, and solvency do not affect the acceptance of going-concern audit opinion.